EXPLORING TECHNIQUES OF FACE-MASK PREPARATION: AN UNIQUE SOCIO-ETHNIC PRODUCT OF ODISHA & ASSAM - Mohapatra, Rudranarayan; Gogoi, Ambeswar; Nisha, B. D.; Chetia, Bikash (International Journal of Psychosocial Rehabilitation, 2020)
Irrespective of integral components of material culture, the social scientist has not shown much inclination towards the scientific study of Face-mask preparation. Again whatever the study has done Adam (1942), Christensen (1955), Boas (1955), Neog (1959), Leiris and Delange (1968), Elwin (1969), Emigh (1981), Pani’s book ’World of Other Faces: Indian Mask’ (1986), Massey and Massey (1989), Mack (1994) s book ’Masks:The Art of Expression’, Barbier (2000), Goswami (2001), Medhi’s ’Mukha Sambandhe Jatkinchit’(2007), David Roy (2015) are all restricted to fundamental traits. Except the exclusiveness ethnicity value description, no cultural similarity campaign to technique of mask production has happen, and neither any state is yet single or jointly demanding its geographical tagging. This paper is trying to explore the technical repro steps followed in face-mask preparation at Assam and Odisha and is trying to cater the distinctiveness of masks and its ethnic market value in present context.